2020
DOI: 10.1007/s10493-020-00568-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rate and resource depletion in the tick Ixodes ricinus in response to temperature

Abstract: Understanding the effects of temperature on the metabolic activity and the rate of depletion of energy reserves by Ixodes ricinus can represent an important contribution to explaining patterns of tick activity and the likely impacts of environmental change on tick and tick-borne disease risk. Here, a cohort of I. ricinus nymphs, males, and females was collected and placed into incubators at temperatures of between 5 and 30 °C. The protein, carbohydrate, total lipid, neutral lipid, and glycogen levels were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In the current study, the influence of temperature on survival was also demonstrated with no questing tick activity observed when the 5-day average temperature exceeded 15 ∘ C and D. reticulatus was shown to be able survive cold shock. The lower lethal temperature for this species was estimated to be between −18 and −20 ∘ C. In contrast, the lower lethal temperature of I. ricinus has been shown to be around −10 to −5 ∘ C (Alasmari & Wall, 2021). As a result, of their cold tolerance, the activity of adult D. reticulatus generally begins in late August/September and continues through to April/May (Rubel et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the current study, the influence of temperature on survival was also demonstrated with no questing tick activity observed when the 5-day average temperature exceeded 15 ∘ C and D. reticulatus was shown to be able survive cold shock. The lower lethal temperature for this species was estimated to be between −18 and −20 ∘ C. In contrast, the lower lethal temperature of I. ricinus has been shown to be around −10 to −5 ∘ C (Alasmari & Wall, 2021). As a result, of their cold tolerance, the activity of adult D. reticulatus generally begins in late August/September and continues through to April/May (Rubel et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…The lower lethal temperature for this species was estimated to be between −18 and −20 °C. In contrast, the lower lethal temperature of I. ricinus has been shown to be around −10 to −5 °C (Alasmari & Wall, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The lowest temperatures that permit the metabolic function of I. ricinus are between −5 °C and −10 °C. These temperatures are probably close to the temperatures that permit the tick’s survival [ 48 ].…”
Section: How Climate Affects Tick Phenology—the Example Of ...mentioning
confidence: 96%
“…This is an effective but time-consuming procedure. The simplest approach is based on the dry weight, preferably in combination with a scutal/dorsal index; this approach has been adequately addressed [11] and morphometric age ratio can also be obtained from living tick specimens.…”
Section: The Evaluation Of the Physiological Stage Of A Tickmentioning
confidence: 99%